Genome-wide identification of wheat ABC1K gene family and functional dissection of TaABC1K3 and TaABC1K6 involved in drought tolerance - Gao, Xiaoran; Zou, Rong; Sun, Haocheng; Liu, Junxian; Duan, Wenjing; Hu, Yingkao; Yan, Yueming (Frontiers in Plant Science, 2022)
Activity of BC1 complex kinase (ABC1K) serves as an atypical kinase family involved in plant stress resistance. This study identified 44 ABC1K genes in the wheat genome, which contained three clades (I-III). TaABC1K genes generally had similar structural features, but differences were present in motif and exon compositions from different clade members. More type II functional divergence sites were detected between clade I and clade III and no positive selection site were found in TaABC1K family. The three-dimensional structure prediction by AlphaFold2 showed that TaABC1K proteins had more α-helixes with a relatively even distribution, and different clade members had differences in the content of secondary structures. The cis-acting element analysis showed that TaABC1K genes contained abundant cis-acting elements related to plant hormones and environmental stress response in the promoter region, and generally displayed a significantly upregulated expression under drought stress. In particular, both TaABC1K3 and TaABC1K6 genes from clade I was highly induced by drought stress, and their overexpression in yeast and Arabidopsis enhanced drought tolerance by suppressing active oxygen burst and reducing photosynthesis impairment. Meanwhile, TaABC1K3 and TaABC1K6 could respectively complement the function of Arabidopsis abc1k3 and abc1k6 mutants and reduce photosynthesis damage caused by drought stress.